2018
DOI: 10.20884/1.oa.2018.14.2.551
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Papain Enzyme Supplement in Feed on Protein Digestibility, Growth and Survival Rate in Sangkuriang Catfish (Clarias sp)

Abstract: The study aimed to assess the effects of Papain Enzyme Supplement in Feed on Protein Digestibity, Growth and Survival Rate of  Sangkuriang Catfish (Clarias sp).  Fingerlings used in the study were acquired from the Center for Freshwater Hatchery and Aquaculture, Muntilan, Central Java, Indonesia. The fingerlings had average weight of 3.43±0.50 g/fish. Completely Randomized Design was used in the experiments with 5 (five) treatment and 3 (three) repetitions. The experimental feed contained 31% of protein and 25… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 14 publications
0
5
1
1
Order By: Relevance
“…Theoretically, a fairly good FCR value ranges from 0.8-1.6 [13]. Compared with other research, the FCR obtained from C. quadricarinatus with the addition of papain enzyme in commercial feed was 1.76 [14]. This figure is lower than the FCR results of this study.…”
Section: Feed Conversion Ratio (Fcr)contrasting
confidence: 77%
See 1 more Smart Citation
“…Theoretically, a fairly good FCR value ranges from 0.8-1.6 [13]. Compared with other research, the FCR obtained from C. quadricarinatus with the addition of papain enzyme in commercial feed was 1.76 [14]. This figure is lower than the FCR results of this study.…”
Section: Feed Conversion Ratio (Fcr)contrasting
confidence: 77%
“…However, after the ANOVA test, there was no significant effect (p= 0.089). Based on other research, adding papain enzyme in commercial feed recorded the highest FUE value of 75.09% [14]. Other research with similar treatment recorded the highest FUE value of 26.11 (±1.24)% [2].…”
Section: Feed Utilization Efficiency (Fue)mentioning
confidence: 93%
“…Sangkuriang) is highly related to feeding availability. Intensive aquaculture feed is the most significant share of cost production, around 50-60% (Rachmawati & Samidjan, 2018). Due to the inefficiency of feed to support growth, the enrichment of the commercial feed with yeast (Saccharomyces cerevisiae) is urgently needed.…”
Section: Introductionmentioning
confidence: 99%
“…Papain is a rich antioxidant, anti-inflammatory, antibacterial, anthelmintic, antipyretic, and immunostimulant with hepatoprotective properties that help to improve cholesterol levels (Cherno et al, 2018;Oloruntola et al, 2020). Studies in aquatic animals demonstrate that including papain improves WG, performance, and diet digestibility (Rachmawati, Prihanto, Setyobudi et al, 2018;Rachmawati & Samidjan, 2018). Oloruntola et al (2020) observed that diets with papaya for broilers promoted the maintenance of normal intestinal microbiota, reduced serum cholesterol and alanine transaminase levels, and increased antioxidant enzyme effects, thereby improving animal performance and health status.…”
Section: Lipidic and Glucose Profilementioning
confidence: 99%